MEMBANGUN BUDAYA ANTIKORUPSI DARI HAL TERKECIL SEJAK DINI - Aisyah Martanti Wulandhari (UNES Law Review, 2019)
Without us knowing, it turns out that Indonesia has been following quite a long time in globalization. There have been many changes that have occurred, starting from the cultural, political, economic system, transportation, lifestyle, especially in the field of technology, and many more. Globalization does have a good influence on Indonesia, but it cannot be denied, globalization also has a bad influence. We can see the culture of westernized life is already widespread among Indonesian people. One of them is selfishness and self harm and is detrimental to the interests of others. A concrete example of this is the act of corruption that seems to have been entrenched in Indonesia. And most of these acts of corruption are actually carried out by people who hold important positions of government, both from the legislative, executive, and judiciary institutions, where they should have received sufficiently higher education and have sufficiently understood that acts of corruption are acts of violation existing community laws and norms. Seeing the current condition of Indonesia, our nation needs future leaders who are free from corruption. Therefore, the nation's children are the hope of the next generation who will later hold the Indonesian government. This anti-corruption character is very good to be instilled in children at an early age of course they start from simple things. This article has been compiled with the aim of exploring ways to develop an anti-corruption culture, especially for Indonesian children at an early age. With the anti-corruption character that has been imprinted in itself since early, it is not impossible that Indonesia will be free from corruption in the future.